Mathematical resilience and learning climate in view of learning style: The impact of improving mathematical reasoning in vocational schools - Halisna, M. Iqbal Maulana; Sunismi, Sunismi; Fuady, Anies (Research and Social Study Institute, 2024)
This research aims to analyze the influence of mathematical resilience and learning climate on the mathematical reasoning of Vocational High School (SMK) students, as well as examine the role of learning style as a moderating variable. Mathematical resilience, which reflects students' ability to persist in facing difficulties in learning mathematics, as well as a positive learning climate, is thought to have an important contribution to mathematical reasoning abilities. The research used a quantitative approach. This research was conducted at two vocational schools in Malang with 200 respondents. Data was collected through mathematical resilience questionnaires, learning climate, learning styles, and mathematical reasoning tests, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Validity and reliability tests showed that all instruments used met the criteria determined, with an AVE value above 0.5 and a Composite Reliability value above 0.7, indicating a valid and reliable instrument. All indicators used in this research also met the significance test with a p-value below 0.05. The research results show that mathematical resilience has a significant influence on students' mathematical reasoning (path coefficient 0.237, t-statistic 3.803, p-value 0.000). The learning climate was also proven to have a positive effect on mathematical reasoning (path coefficient 0.287, t-statistic 4.125, p-value 0.000). However, learning style does not significantly moderate the influence of mathematical resilience on mathematical reasoning. Still, it plays a moderate role in the relationship between learning climate and mathematical reasoning (t-statistic 2.102, p-value 0.036). These findings provide insight into the importance of learning strategies that support resilience and learning climate to improve students' mathematical reasoning abilities at the vocational secondary education level.